2018
DOI: 10.1007/s00023-018-0666-6
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries Versus Conservation Laws in Dynamical Quantum Systems: A Unifying Approach Through Propagation of Fixed Points

Abstract: We unify recent Noether-type theorems on the equivalence of symmetries with conservation laws for dynamical systems of Markov processes, of quantum operations, and of quantum stochastic maps, by means of some abstract results on propagation of fixed points for completely positive maps on C *-algebras. We extend most of the existing results with characterisations in terms of dual infinitesimal generators of the corresponding strongly continuous one-parameter semigroups. By means of an ergodic theorem for dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The first statement is regarding the relationship between the conserved quantities J and the Kraus of operators of E. It is a generalization of a theorem for fixed points of faithful channels [24,[61][62][63][64], which states that a conserved quantity J with eigenvalue ∆ = 0 commutes with all of the Kraus operators. It is shown that conserved quantities with ∆ = 0 commute up to a phase.…”
Section: Faithful Channelsmentioning
confidence: 99%
“…The first statement is regarding the relationship between the conserved quantities J and the Kraus of operators of E. It is a generalization of a theorem for fixed points of faithful channels [24,[61][62][63][64], which states that a conserved quantity J with eigenvalue ∆ = 0 commutes with all of the Kraus operators. It is shown that conserved quantities with ∆ = 0 commute up to a phase.…”
Section: Faithful Channelsmentioning
confidence: 99%
“…Another topic which has drown attention in the last years is the study of the fixed points of the evolution: they are relevant for the asymptotics of the evolution of quantum systems ( [10]) and whether or not they are a W * -algebra has implications, for instance, on the relationship between conserved quantities and symmetries of the semigroup (see [2] about the general problem of when fixed points are an algebra and [12] for a discussion about Noether-type results in the context of quantum channels). Fixed points are well understood in the case of positive recurrent semigroups ([4, 9, 14]), while less is known for general semigroups ( [1,3,11]).…”
Section: Introductionmentioning
confidence: 99%